2017
DOI: 10.1093/cz/zox031
|View full text |Cite|
|
Sign up to set email alerts
|

Wolf predation on wild ungulates: how slope and habitat cover influence the localization of kill sites

Abstract: Based on data collected along the Ligurian Apennines and Alps (N-W Italy), we analysed the main environmental and human-related factors influencing the distribution of kill sites of the wolf Canis lupus. We mapped and digitized 62 kill sites collected during 2007–2016. Around each kill site, we defined a buffer corresponding to the potential hunting area of wolves. We compared kill site plots and an equal number of random plots. We formulated a model of kill site distribution following an approach presence ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
3
16
1
Order By: Relevance
“…In agreement with our results, previous works [50,53] have reported that, in dense forest cover, wild ungulates are more wary than in open areas and that this condition favours predator detection due to their noisier approach [54]; moreover, previous studies have shown that roe deer presence in the wolf diet increased with an increase in open areas [55].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our results, previous works [50,53] have reported that, in dense forest cover, wild ungulates are more wary than in open areas and that this condition favours predator detection due to their noisier approach [54]; moreover, previous studies have shown that roe deer presence in the wolf diet increased with an increase in open areas [55].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported positive relationships between open habitats and wolf presence [61], kills, and scavenging sites [50,52,62,63], suggesting that extended open areas favour coursing behaviour, allowing wolves to engage in cooperative hunting strategies and to better choose vulnerable individuals [52,63]. Differently, in our case study, open habitats (i.e., pastures and natural grasslands) negatively affected wolf responsiveness in winter.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…, a risky place is one where there is a high probability of encountering and being killed by a predator. For example, elk select for areas with abundant forage biomass in summer (Hebblewhite & Merrill, 2009;Smolko 2014), which is where we found a higher probability of elk being present in the scat of all species; we also found elk being in wolf scats associated with rugged terrain, which is where Torretta et al, (2018) also reported wolf kill sites, suggesting ruggedness reduced agility to navigate in steep terrain.…”
Section: Discussionmentioning
confidence: 51%